Long‐term safety and efficacy of the PI3K inhibitor copanlisib in patients with relapsed or refractory indolent lymphoma: 2‐year follow‐up of the CHRONOS‐1 study. Issue 4 (16th January 2020) - Dreyling, Martin; Santoro, Armando; Mollica, Luigina; Leppä, Sirpa; Follows, George; Lenz, Georg; Kim, Won Seog; Nagler, Arnon; Dimou, Maria; Demeter, Judit; Özcan, Muhit; Kosinova, Marina; et al.
Abstract: Safety profiles of oral PI3K inhibitors have resulted in US FDA black box warnings regarding fatal/serious toxicities. The approved intravenous PI3K inhibitor copanlisib has low incidence of severe toxicities and no black box warnings, but chronic treatment effects were unknown. We provide an update on safety and efficacy of copanlisib with a minimum 2‐year follow‐up of the CHRONOS‐1 study. A total of 142 patients with histologically confirmed indolent B‐cell lymphoma who had relapsed after or were refractory to ≥2 prior treatments received intravenous copanlisib 60 mg on days 1, 8, and 15 (28‐day cycle). The primary efficacy endpoint was objective response rate (ORR) after ≥4 cycles (independent assessment). The predominant histology was follicular lymphoma (n = 104). The ORR was 60.6% (seven additional complete responses since primary analysis). Secondary endpoints of median duration of response, progression‐free survival, and overall survival were 14.1 months (median follow‐up, 16.1 months), 12.5 months (median follow‐up, 14.0 months), and 42.6 months (median follow‐up, 31.5 months), respectively. Median safety follow‐up was 6.7 months; 26% of patients received treatment for >1 year. Common treatment‐emergent adverse events (TEAEs) (all grade/grade 3/grade 4) were transient hyperglycemia (50.0%/33.1%/7.0%), diarrhea (35.2%/8.5%/0%), transient hypertension (29.6%/23.9%/0%), and neutropenia (28.9%/9.2%/14.8%). Serious AEs were largely unchanged, with no new cases of pneumonitis (4.2%), diarrhea (2.8%), or grade 5 events. Note, TEAEs showed no evidence for increased incidence or worsening following longer exposure in patients treated >1 year. Long‐term follow‐up of patients with relapsed/refractory indolent B‐cell lymphoma treated with intravenous copanlisib demonstrated durable, enhanced responses without evidence of worsening TEAEs, as reported for orally administered PI3K inhibitors.